PENINGKATAN PEMBELAJARAN GERAK DASAR TOLAK PELURU MELALUI PERMAINAN TARSAN PADA SISWA KELAS V SD NEGERI 3 LEBAK KECAMATAN PAKIS AJI (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
Research method used is model of research of class action ( PTK) with aim to to look for the trouble-shooting practically orienting at action. Where each;every sikuls consisted of by 4 phase that is (1) planning phase, (2) action Phase, (3) observation Phase, (4) phase refleksi to form of game tarsan (target goals) to student of class of V of Elementary School Country 3 Lebak. Data collecting by using kuesioner obtained from evaluation of Study expert, Cycle I (30 student of Class of V SD Country 3 Lebak), and Cycle II ( 30 student of Class of V SD Country 3 Lebak). Data in the form of research result regarding the quality of product, suggestion for the repair of product, and result of admission filling kuesioner by student. Technics analyse the data used is descriptive presentase to express the aspect psikomotorik, cognate, and afectiv student. Result of obtainable Research of data from result learn or complete learn the student of equal to 64,00% (enough) at cycle I and 86,67 % (good) of Cycle II, data evaluate the assessment of study expert at Cycle I of equal to 43,50 % (enough) of while Cycle II obtained result 84,00 % (good) while result of admission filling of kuesioner student at cycle I equal to 57,33 % (enough) while at cycle II equal to 87,33 % (good). From data of result of research above inferential that elementary motion study weight throw the game tarsan ( target goals) to student of class of V of Elementary SchoolÂ  Country 3 Lebak of Sub-Province Jepara with the good result.